Peningkatan Pengetahuan pada Kader tentang Pemilihan Obat pada Pembelian Secara Online - Erawati, Ambar Dwi; Manurung, Mona Tiorina; Zulaika, Chusnul; Sugiharto, Sigit (Jurnal ABDIMAS-HIP Pengabdian Kepada Masyarakat, 2024)
Every human being has a desire to be healthy. Efforts to get healing by buying their own medicine are one of the options that people are interested in. Medicine is a chemical substance that has an effect. Drugs if consumed freely can be given drug doses (over and the risk of mismatch between the disease and the drug consumed (medication error). Consumption of drugs without a doctor's prescription or choosing yourself according to the symptoms faced, can result in errors in drug consumption that can be dangerous. People need to know how to choose drugs that can be purchased freely. Counseling activities were carried out on 20 cadres of Bambankerep Village. The stages of activity begin with the preparation of counseling, implementation and evaluation. From the results of the activity there was an increase in knowledge about drug classes and types of drugs rose to 30%. The hope is that cadres can transmit information to the people in their area so that people understand about drug selection.